Meadows or asphalt road - does momentary affective well-being vary with immediate physical environment?: Results from a geographic ecological momentary assessment study in three metropolitan areas in Germany - Mascherek, Anna; Luong, Gloria; Wrzus, Cornelia; Riediger, Michaela; Kühn, Simone (Environmental research, 2025)
We investigated the association between the immediate physical environment of individuals and individual fluctuations of momentary affective well-being in everyday life with a focus on medium sized metropolitan areas in Europe representing a typical living environment of a large proportion of the world’s population. The sample comprised 365 individuals (54.8 % female) with participants ranging from 14.08 to 88.27 years of age (M = 43.9, SD = 20.9). In an geographic ecological momentary assessment (GEMA), participants were prompted six times a day on at least 9 days over the course of 3 weeks, covering a total of six weekdays and three weekend days on mobile phones to report their momentary affective well-being. Urban land use categories (forest, water, urban green) were assessed with GPS-localization as environmental variables. Additionally, sunshine, rainfall, whether participants were inside or outside as well as whether they were alone or had company were included into the analyses. We used dynamic structural equation modelling to model the inter- and intraindividual differences as well as fluctuations and assess potential covariates while acknowledging the autoregressive nature of affect. The results showed that on individual level, fluctuations of momentary affective well-being were associated with sunshine, having company and travelling. No significant association emerged for urban green, forest, and water neither within individuals nor between. Methodological as well as conceptual implications are discussed and an interpretation of the present findings are provided.